2014
DOI: 10.5588/pha.13.0075
|View full text |Cite
|
Sign up to set email alerts
|

Profile of tuberculosis patients with delayed sputum smear conversion in the Pacific island of Vanuatu

Abstract: Global implementation of the DOTS strategy has resulted in a decline in tuberculosis (TB) incidence rates. 1 However, total patient numbers have not declined, and rates remain high in areas affected by human immunodeficiency virus (HIV) infection, poverty and drug-resistant TB. 2 Despite the adoption of the DOTS strategy in 1999-2000, progress towards global TB control targets has been slow in the Pacific region, with 16 534 cases (165 per 100 000 population) notified in 2011 compared to 4017 (68/100 000) in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…Other potential explanations for non-conversion of sputum smear at the end of the intensive phase of TB treatment are: poor supervision of the initial phase of therapy, poor patient adherence, poor quality of anti-TB drugs, doses of anti-TB drugs below the recommended range, co-morbid conditions, drug-resistant M. tuberculosis that is not responding to first-line treatment and heavy initial bacillary load [ 4 ]. Heavy initial bacillary load has been documented (as in our study) as an important risk factor of delay in sputum smear conversion at the end of intensive phase of TB treatment [ 6 , 7 , 15 - 17 ]. So, to avoid non-conversion at the end of the initial phase of TB treatment, patients should be diagnosed early and treated.…”
Section: Discussionmentioning
confidence: 55%
“…Other potential explanations for non-conversion of sputum smear at the end of the intensive phase of TB treatment are: poor supervision of the initial phase of therapy, poor patient adherence, poor quality of anti-TB drugs, doses of anti-TB drugs below the recommended range, co-morbid conditions, drug-resistant M. tuberculosis that is not responding to first-line treatment and heavy initial bacillary load [ 4 ]. Heavy initial bacillary load has been documented (as in our study) as an important risk factor of delay in sputum smear conversion at the end of intensive phase of TB treatment [ 6 , 7 , 15 - 17 ]. So, to avoid non-conversion at the end of the initial phase of TB treatment, patients should be diagnosed early and treated.…”
Section: Discussionmentioning
confidence: 55%
“…Our study is limited in that the assessment was based solely on information acquired from patient registers with some essential risk factor information such as the outcome of this study which is post-treatment smear grades missing from the MyTB system. Several studies had reported that at the end of the intensive TB treatment, heavy original bacillary load was recorded as a significant risk factor for delay in sputum smear transformation [44–47] . Future improvements or upgrade of MyTB should consider the inclusion of pre-treatment smear grades in the information system.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies had reported that at the end of the intensive TB treatment, heavy original bacillary load was recorded as a significant risk factor for delay in sputum smear transformation. [44][45][46][47] Future improvements or upgrade of MyTB should consider the inclusion of pre-treatment smear grades in the information system. In addition, not all patients who were smearpositive had sputum culture results.…”
Section: Limitationsmentioning
confidence: 99%
“…Research in Vanuatu found that an emphasis on patient education that encouraged treatment adherence improved sputum conversion among delayed sputum converters. [ 30 ] In addition, TB control programs should be integrated with programs to encourage patients to stop smoking, especially for TB patients with low levels of education who are young to adult smokers. TB control programs should also include treatment follow-up for TB patients with DM to ensure appropriate TB treatment.…”
Section: Discussionmentioning
confidence: 99%